Good Corporate Governance and Corporate Social Responsibility on Firm Value - Muslim Muslim; Yaya Sonjaya (Bata Ilyas Journal of Accounting, 2023)
This study aims to empirically examine the influence of independent commissioners and corporate social responsibility on firm value in state-owned and manufacturing companies listed on the Indonesia Stock Exchange. The population in this study are state-owned and manufacturing companies listed on the Indonesia Stock Exchange (IDX). The selection of this research sample was carried out by purposive sampling method. Based on the existing criteria, 30 companies became the research sample. Data were analyzed using descriptive statistical tests, classical assumption tests (normality test, heteroscedasticity test, multicollinearity test) and multiple linear regression analysis, coefficient of determination test, partial test and simultaneous test, which were processed using the SPSS program. The data analysis results show that Good Corporate Governance, proxied by independent commissioners, has a positive and significant influence on the value of BUMN and manufacturing companies listed on the Indonesia Stock Exchange. Meanwhile, Corporate Social Responsibility has a positive and insignificant effect on the value of BUMN and manufacturing companies listed on the Indonesia Stock Exchange.Keywords:Good Corporate Governance, Corporate Social Responsibility, Firm Value